Re-Chord: A Self-stabilizing Chord Overlay Network - Kniesburges, Sebastian; Koutsopoulos, Andreas; Scheideler, Christian (Theory of Computing Systems)
The Chord peer-to-peer system is considered, together with CAN, Tapestry and Pastry, as one of the pioneering works on peer-to-peer distributed hash tables (DHT) that inspired a large volume of papers and projects on DHTs as well as peer-to-peer systems in general. Chord, in particular, has been studied thoroughly, and many variants of Chord have been presented that optimize various criteria. Also, several implementations of Chord are available on various platforms. Though Chord is known to be very efficient and scalable and it can handle churn quite well, no protocol is known yet that guarantees that Chord is self-stabilizing, i.e., the Chord network can be recovered from any initial state in which the network is still weakly connected. This is not too surprising since it is known that the Chord network is not locally checkable for its current topology. We present a slight extension of the Chord network, called Re-Chord (reactive Chord), that turns out to be locally checkable, and we present a self-stabilizing distributed protocol for it that can recover the Re-Chord network from any initial state, in which the n peers are weakly connected, in O(nlogn) communication rounds. We also show that our protocol allows a new peer to join or an old peer to leave an already stable Re-Chord network so that within O(logn)^2) communication rounds the Re-Chord network is stable again.

Randomized Online Algorithms for Set Cover Leasing Problems - Abshoff, Sebastian; Markarian, Christine; Meyer auf der Heide, Friedhelm (Proceedings of the 8th Annual International Conference on Combinatorial Optimization and Applications (COCOA))
In the leasing variant of Set Cover presented by Anthony et al.[1], elements U arrive over time and must be covered by sets from a familyF of subsets of U. Each set can be leased for K different periods of time.Let |U| = n and |F| = m. Leasing a set S for a period k incurs a cost ckS and allows S to cover its elements for the next lk time steps. The objectiveis to minimize the total cost of the sets leased, such that elements arrivingat any time t are covered by sets which contain them and are leased duringtime t. Anthony et al. [1] gave an optimal O(log n)-approximation forthe problem in the offline setting, unless P = NP [22]. In this paper, wegive randomized algorithms for variants of Set Cover Leasing in the onlinesetting, including a generalization of Online Set Cover with Repetitionspresented by Alon et al. [2], where elements appear multiple times andmust be covered by a different set at each arrival. Our results improve theO(log2(mn)) competitive factor of Online Set Cover with Repetitions [2]to O(log d log(dn)) = O(logmlog(mn)), where d is the maximum numberof sets an element belongs to.

Quality of Service in Network Creation Games - Cord-Landwehr, Andreas; Mäcker, Alexander; Meyer auf der Heide, Friedhelm (Proceedings of the 10th International Conference on Web and Internet Economics (WINE))
Network creation games model the creation and usage costs of networks formed by n selfish nodes. Each node v can buy a set of edges, each for a fixed price α > 0. Its goal is to minimize its private costs, i.e., the sum (SUM-game, Fabrikant et al., PODC 2003) or maximum (MAX-game, Demaine et al., PODC 2007) of distances from v to all other nodes plus the prices of the bought edges. The above papers show the existence of Nash equilibria as well as upper and lower bounds for the prices of anarchy and stability. In several subsequent papers, these bounds were improved for a wide range of prices α. In this paper, we extend these models by incorporating quality-of-service aspects: Each edge cannot only be bought at a fixed quality (edge length one) for a fixed price α. Instead, we assume that quality levels (i.e., edge lengths) are varying in a fixed interval [βˇ,β^] , 0 series = LNCS

Provider Competition in Infrastructure-as-a-Service - Künsemöller, Jörn; Brangewitz, Sonja; Karl, Holger; Haake, Claus-Jochen (Proceedings of the 2014 IEEE International Conference on Services Computing (SCC))
This paper explores how cloud provider competition inﬂuences instance pricing in an IaaS (Infrastructure-as-a-Service) market. When reserved instance pricing includes an on-demand price component in addition to a reservation fee (two-part tariffs), different providers might offer different price combinations, where the client’s choice depends on its load proﬁle. We investigate a duopoly of providers and analyze stable market prices in two-part tariffs. Further, we study offers that allow a speciﬁed amount of included usage (three-part tariffs). Neither two-part nor three-part tariffs produce an equilibrium market outcome other than a service pricing that equals production cost, i.e., complex price structures do not signiﬁcantly affect the results from ordinary Bertrand competition.

Oblique incidence of semi-guided waves on rectangular slab waveguide discontinuities: A vectorial QUEP solver - Hammer, Manfred (Optics Communications)
The incidenceofthin-film-guided, in-planeunguidedwavesatobliqueanglesonstraightdiscontinuities of dielectricslabwaveguides,anearlyproblemofintegratedoptics,isbeingre-considered.The3-D frequencydomainMaxwellequationsreducetoaparametrizedinhomogeneousvectorialproblemona 2-D computationaldomain,withtransparent-influx boundaryconditions.Weproposearigorousvec- torial solverbasedonsimultaneousexpansionsintopolarizedlocalslabeigenmodesalongthetwo orthogonal crosssectioncoordinates(quadridirectionaleigenmodepropagationQUEP).Thequasi-ana- lytical schemeisapplicabletoconfigurations with — in principle — arbitrary crosssectiongeometries. Examples forahigh-contrastfacetofanasymmetricslabwaveguide,forthelateralexcitationofa channel waveguide,andforastepdiscontinuitybetweenslabwaveguidesofdifferentthicknessesare discussed.
Keywords: tet_topic_waveguide; tet_topic_numerics

On Variants of the Page Migration Problem - Feldkord, Björn

Dietary Lipid Intake only Partially Influences Variance in Serum Phospholipid Fatty Acid Composition in Adolescents: Impact of Other Dietary Factors - Vyncke, Krishna; Huybrechts, Inge; Van Winckel, Myriam; Cuenca Garcia, Magdalena; Labayen, Idoia; Gottrand, Frederic; Widhalm, Kurt; Leclercq, Catherine; Libuda, Lars; Manios, Yannis; Sjostrom, Michael; Molnar, Denes; et al. (Lipids)

SentiBA: Lexicon-based Sentiment Analysis on German Product Reviews - Dollmann, Markus; Geierhos, Michaela (Workshop Proceedings of the 12th Edition of the KONVENS Conference)
In this paper, we describe our system developed for the GErman SenTiment AnaLysis shared Task (GESTALT) for participation in the Maintask 2: Subjective Phrase and Aspect Extraction from Product Reviews. We present a tool, which identifies subjective and aspect phrases in German product reviews. For the recognition of subjective phrases, we pursue a lexicon-based approach. For the extraction of aspect phrases from the reviews, we consider two possible ways: Besides the subjectivity and aspect look-up, we also implemented a method to establish which subjective phrase belongs to which aspect. The system achieves better results for the recognition of aspect phrases than for the subjective identification.
Keywords: corpus linguistics; sentiment analysis

Joining with electrochemical support (ECUF): Cold pressure welding of copper - Ebbert, Christoph; Schmidt, H. C.; Rodman, D.; Nuernberger, F.; Homberg, W.; Maier, H. J.; Grundmeier, Guido (JOURNAL OF MATERIALS PROCESSING TECHNOLOGY)
Joining metals using electrochemical support (ECUF) is a new process for cold pressure welding sheets and parts. This new process is based on an electrochemical in-line surface treatment followed by incremental pilger rolling. The ECUF process intends to cold pressure weld materials under optimized conditions. Oxide layers on metal surfaces are known to inhibit the formation of cold pressure welds. The in-line electrochemical treatment will be used to remove these surface oxides for specific engineering metals and alloys. Hence, an improved pressure weld formation at lower forces and smaller reduction ratios is expected for the electrochemically treated surfaces. Using a more flexible pressure welding process, the number of applications could be greatly improved. First tests with copper were performed to analyse the efficiency of the proposed electrochemical surface treatments. Two electrochemical treatments, the cathodic oxide-reduction and cyclovoltammetric oxide-reduction, were compared with conventional treatments (degreasing and scratch brushing) regarding their influence on the cold pressure welding process of copper. The weld strength of lap welds has been investigated as well as the necessary reduction threshold to form a weld. It was found that the electrochemical oxide reduction resulted in higher weld strength. The results of scanning electron microscopy (SEM) and energy dispersive analysis of X-rays (EDX) indicate that surface oxides were successfully removed by the electrochemical surface treatments. (C) 2014 Elsevier B.V. All rights reserved.

Beitrag zur Kennwertermittlung für die numerische Simulation des Tragverhaltens von Halbhohlstanznietverbindungen unter Crashbelastung - Hein, David
Bei der Umsetzung von innovativen Leichtbaukonzepten finden verstärkt mechanische Fügeverfahren Anwendung. Folglich werden im Automobilbau, neben den konventionellen Fügeverfahren wie dem Widerstandspunktschweißen, mechanische Verbindungstechniken, wie z.B. das Halbhohlstanznieten eingesetzt.Für den effektiven Einsatz dieser Fügetechniken insbesondere in crashrelevanten Bereichen fehlen jedoch bislang Verbindungskennwerte, die eine Vorhersage über das Tragverhalten dieser Verbindungen ermöglichen. Das Ziel dieser Arbeit war es, das Tragverhalten von Halbhohlstanznietverbindungen für den Lastfall Crash zu charakterisieren und eine Methode aufzuzeigen, mit deren Hilfe es möglich ist, das experimentell ermittelte Verhalten rechnerisch abzuschätzen. Diese Arbeit beinhaltet, neben der experimentellen Ermittlung von Werkstoffkennwerten, die Ergebnisse zur Charakterisierung der Tragfähigkeit von Halbhohlstanznietverbindungen unter Crashbelastung. Dabei wird neben der einfach überlappten Zugscher- und Schälzugprobe das patentierte LWF-KS-2-Prüfkonzept eingesetzt, welches Tragfähigkeitsuntersuchungen unter Berücksichtigung der Lasteinleitungsrichtung und der Belastungsgeschwindigkeit erlaubt. Als Versuchswerkstoffe kamen dabei der mikrolegierte Stahlwerkstoff HC340LA,der Bake-Hardening-Stahl HC180BD, der Dualphasenstahl HCT600X sowie die Aluminiumlegierungen EN AW-6014 und EN AW-6060 zum Einsatz. Die experimentell ermittelten Verbindungskennwerte dienten unmittelbar als Eingangsdaten für die rechnergestützte Vorhersage des Trag- und Versagensverhaltens von Halbhohlstanznietverbindungen. Aufbauend darauf wurde in der vorliegenden Arbeit eine Methodik zur Entwicklung und Optimierung eines numerischen Ersatzmodells für Halbhohlstanznietverbindungen unter Crashbelastung dargestellt.
Keywords: Halbhohlstanznietverbindungen; Crash; Crashbelastung

World Cultural Heritage: Cultural Identity and the War on Works of Art. Introduction, Sketch of Problems and Objects - Seng, Eva- Maria (The Challenge of the Object. Section 6, The Proceedings of the 33. International Congress in the History of Art. Nuremberg, 15.-20. July 2012. Comité International d’Histoire de l’Art, CIHA, Bd. 2)

Nanoscale Structure of Si/SiO2/Organics Interfaces - Steinrück, Hans-Georg; Schiener, Andreas; Schindler, Torben; Will, Johannes; Magerl, Andreas; Konovalov, Oleg; Li Destri, Giovanni; Seeck, Oliver H.; Mezger, Markus; Haddad, Julia; Deutsch, Moshe; Checco, Antonio; et al. (ACS Nano)

Interface Engineering of Molecular Charge Storage Dielectric Layers for Organic Thin-Film Memory Transistors - Khassanov, Artoem; Schmaltz, Thomas; Steinrück, Hans-Georg; Magerl, Andreas; Hirsch, Andreas; Halik, Marcus (Advanced Materials Interfaces)

Tuning the molecular order of C60-based self-assembled monolayers in field-effect transistors - Schmaltz, Thomas; Khassanov, Artoem; Steinrück, Hans-Georg; Magerl, Andreas; Hirsch, Andreas; Halik, Marcus (Nanoscale)

Pseudorotational Epitaxy of Self-Assembled Octadecyltrichlorosilane Monolayers on Sapphire (0001) - Steinrück, Hans-Georg; Magerl, A.; Deutsch, M.; Ocko, B. M. (Physical Review Letters)

Towards a Production System Specification Technique for Functionally Graded Components - Petersen, Marcus; Bauer, Frank; Hess, Stefan; Gausemeier, Jürgen; Gräßler, Iris (Proceedings of the DESIGN 2014 - 13th International DESIGN Conference | Volume 2)
Functional gradation means a tailored distribution of properties over the spatial dimensions of a component based on a complex manufacturing process chain. The synthetisation of these processes requires a framework that generates numerous information for the production system elaboration during the further design phases. Therefore a production system specification technique for functionally graded components is presented. The specification technique enables the visualisation of the resulting process chain with all information in a descriptive manner and offers an interface for Microsoft Visio.

Early Analysis of the System Dynamics of Self-Optimizing Systems - Vaßholz, Mareen; Gräßler, Iris (Proceedings of the DESIGN 2014, 13th International DESIGN Conference, Band 2)

Eigenverstärkte Thermoplastverbunde - Verbundwerkstoffe (Teil 2) - Heim, Hans-Peter; Ries, Angela; Schöppner, Volker; Wibbeke, Andrea; Turek, Stefan; Damanik, Hogenrich; Mahnken, Rolf; Dammann, Christian; Wünsch, Olaf; Al-Baldawi, Ammar; Rohde, Björn; Brückner-Foit, Angelika; et al. (Kunststoffe 104 (3/2014))
Anhand von Forschungsergebnissen aus dem Sonderforschungsbereich Transregio 30 wird dargestellt, wie Verbunde aus eigenverstärkten teilkristallinen oder hochgereckten amorphen Folien und Gewebe für Leichtbauanwendungen hergestellt und welche Eigenschaften erreicht werden können. Eine lokal differenzielle, thermo-mechanische Prozessführung ist sehr effizient variierbar, und somit lassen sich gradierte Eigenschaften im Sinne einer Funktionalisierung einstellen.

Self-Reinforced Thermoplastic Composites - Composite Materials (Part 2) - Heim, Hans-Peter; Ries, Angela; Schöppner, Volker; Wibbeke, Andrea; Turek, Stefan; Damanik, Hogenrich; Mahnken, Rolf; Dammann, Christian; Wünsch, Olaf; Al-Baldawi, Ammar; Rohde, Björn; Brückner-Foit, Angelika; et al. (Kunststoffe international 104 (3/2014))
Anhand von Forschungsergebnissen aus dem Sonderforschungsbereich Transregio 30 wird dargestellt, wie Verbunde aus eigenverstärkten teilkristallinen oder hochgereckten amorphen Folien und Gewebe für Leichtbauanwendungen hergestellt und welche Eigenschaften erreicht werden können. Eine lokal differenzielle, thermo-mechanische Prozessführung ist sehr effizient variierbar, und somit lassen sich gradierte Eigenschaften im Sinne einer Funktionalisierung einstellen.

Self-Reinforced Thermoplastic Composites - Composite Materials (Part 1) - Heim, Hans-Peter; Ries, Angela; Schöppner, Volker; Wibbeke, Andrea; Turek, Stefan; Damanik, Hogenrich; Mahnken, Rolf; Dammann, Christian; Wünsch, Olaf; Al-Baldawi, Ammar; Rohde, Björn; Brückner-Foit, Angelika; et al. (Kunststoffe international 104 (2/2014))
Mit eigenverstärkten Thermoplasten ist es möglich, Verbundsysteme herzustellen, die im Unterschied zu klassischen Faserverbundwerkstoffen keine Fremdfasern zur Verstärkung enthalten. Stattdessen werden thermoplastische Fasern oder Bändchen z.B. aus PP oder PE in einer identischen Matrix eingesetzt. Damit eröffnet sich ein hohes Leichtbaupotenzial bei gleichzeitig sehr guter Rezyklierbarkeit.